DOUBLE PRIMARY – THE PATTERN OF CARE, AND EPIDEMIOLOGY: EXPERIENCE FROM A TERTIARY CANCER CARE CENTER - DUTTA, SHATARUPA; BANERJEE, SAPTARSHI; BERA, ANJAN; MANDAL, SRIKRISHNA; BANERJEE, CHANDRIMA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The importance and relevance of double primary are increasing with time as the increasing use of advanced diagnostic investigation and an increasing number of cancer survivors lead to an increase in double primary malignancy. Methods: We have collected data retrospectively from our own departmental patient’s record section from January 2011 to December 2021. All the details such as histopathology of both the malignancy, site of primary and secondary cancer, the time gap between the two cancer, clinical stage, and treatment received, along with demographic details have been recorded. Patients are divided into two categories either synchronous or metachronous when a second tumor develops either simultaneously or within 6 months of the diagnosis of the first tumor or 6 months after the diagnosis of the primary malignancy, respectively. Results: The total number of registered cases in one decade at our institute was 25,638 and among them were 41 double primary cases (0.16%). Twenty-two cases were metachronous (59%) and 19 cases (41%) were synchronous double primary. The most common site of double primary site was the head and neck region (38 %) followed by the lung, and esophagus (13% each), and the least common site was the colon (<1%). In the case of metachronous double primary, the mean time interval (the time gap between two cancer devolvement) was 7.4 years with a range of 2–19 years. The majority of the patients are treated with curative intention. Conclusions: The incidence of double primary is increasing over time. The management of double primary should be supervised by a multidisciplinary tumor board and more research is needed in the areas of epidemiology and treatment.